Exploring Traditional Knowledge and Potential Uses of Local Freshwater Algae and Aquatic Plants in Thai Wetland Communities - Pasin Norkum Ai; Angkhana Inta; Sarana Rose Sommano; Kittiya Phinyo; Kritsana Duangjan; Tibet Tangpao (Diversity)
This study explored the ecological and cultural significance of Thailand’s wetlands, particularly the Nong Bong Kai Non-Hunting Area and the Lower Songkhram River. These areas were essential for biodiversity, flood prevention, and supporting local livelihoods, serving as food sources, biofertilizers, and natural water purifiers. However, these wetlands faced mounting threats from pollution, habitat loss, and climate change, jeopardising their ecological health and biodiversity. Ethnobotanical surveys were conducted to assess regional and demographic patterns in using and recognising algae and aquatic plants. The collected data highlighted traditional ecological knowledge held primarily by older community members. Principal component analysis (PCA) was employed to analyse generational differences in knowledge and utilisation, focusing on the potential generational knowledge gap due to migration trends among younger individuals. The study revealed significant biodiversity differences between the wetland areas, with Nong Bong Kai exhibiting greater diversity in aquatic plant species. Older residents demonstrated higher recognition and use of algae and aquatic plants for sustainable practices, though a generational knowledge gap was evident. This gap suggested that local ecological knowledge may be at risk as younger residents migrate to urban areas. This research underscored the need for conservation and educational initiatives to bridge generational gaps and engage younger generations in resource management. By integrating local cultural practices and focusing on high-impact species like Lemna perpusilla Torr. and Hydrilla verticillate (L.f.) Royle, region-specific conservation efforts could enhance wetland sustainability, preserve biodiversity, and support ecosystem health in Thailand’s wetland regions.